Studi Korelasi Status Gizi dengan Kejadian Anemia pada Ibu Hamil - Natiqotul Fatkhiyah; Umi Salamah; Arriani Indrastuti; Loviana Nurfiati (LPPM Hang Tuah Pekanbaru, 2022)
The incidence of anemia in pregnancy is a nutritional problem that affects human resources and has an impact on maternal and child health. Anemia in pregnant women is strongly associated with maternal and infant mortality and morbidity, including the risk of miscarriage, stillbirth, prematurity and low birth weight. To identify the relationship between nutritional status and the incidence of anemia in pregnant women at the Slawi Public Health Center, Tegal Regency. The study sample used purposive sampling of 30 pregnant women. Test the relationship of variables using chi-square with a p value of 0.01, which means that there is a correlation between nutritional status and the incidence of anemia in pregnant women.